Non-covalent Methods of Engineering Optical Sensors Based on Single-Walled Carbon Nanotubes - Gillen, Alice J.; Boghossian, Ardemis A. (Frontiers in Chemistry, 2019)
Optical sensors based on single-walled carbon nanotubes (SWCNTs) demonstrate tradeoffs that limit their use in in vivo and in vitro environments. Sensor characteristics are primarily governed by the non-covalent wrapping used to suspend the hydrophobic SWCNTs in aqueous solutions, and we herein review the advantages and disadvantages of several of these different wrappings. Sensors based on surfactant wrappings can show enhanced quantum efficiency, high stability, scalability, and diminished selectivity. Conversely, sensors based on synthetic and bio-polymer wrappings tend to show lower quantum efficiency, stability, and scalability, while demonstrating improved selectivity. Major efforts have focused on optimizing sensors based on DNA wrappings, which have intermediate properties that can be improved through synthetic modifications. Although SWCNT sensors have, to date, been mainly engineered using empirical approaches, herein we highlight alternative techniques based on iterative screening that offer a more guided approach to tuning sensor properties. These more rational techniques can yield new combinations that incorporate the advantages of the diverse nanotube wrappings available to create high performance optical sensors.